Moderasi Agama dalam Perspektif Jamaah Tabligh, Muhammadiyah, dan Nahdlatul Ulama Lampung - Muttaqin, Ahmad; Zaeny, Ahmad; Salim, Luthfi (Kamaya: Jurnal Ilmu Agama, 2025)
Islamic mass organizations (Ormas) that exist and develop in the midst of society also influence the dynamics of social life, especially in the context of religious moderation. This study aims to analyze the perspectives of three Islamic mass organizations in Lampung, namely Jamaah Tabligh, Muhammadiyah, and Nahdlatul Ulama on religious moderation. This study uses a case study method with primary data obtained through in-depth interviews with figures from each of these mass organizations. The results of the study show that by using their perspectives on the differences between Islamic mass organizations, views on the term “infidel”, and views on the relationship between religion and state (Pancasila), it is concluded that these three mass organizations have a moderate attitude towards differences between Islamic mass organizations, by prioritizing the principle of mutual respect and appreciation in worship and organization. Jamaah Tabligh emphasizes unity among Muslims despite differences in carrying out worship, while Muhammadiyah and NU also recognize this diversity, but emphasize the importance of preaching in an inclusive manner. Regarding the view on the term “kafir”, Jamaah Tabligh and NU use the term contextually in the early history of Islam, while Muhammadiyah emphasizes more on the attitude of tolerance between religious communities. The three mass organizations also agree that Pancasila as the foundation of the Indonesian state is the right foundation, which allows the integration of religious values ​​in national and state life, without forgetting diversity. Overall, this study shows that moderation varies according to the perspectives of three mass organizations in Lampung, namely Jamaah Tabligh, Muhammadiyah, and Nahdlatul Ulama, reflected in an inclusive and harmonious attitude towards differences, both in aspects of worship, social views, and politics. Such views can also prevent conflict in the midst of society due to differences in views.